Progressive gut microbiota shifts and functional alterations across aging stages and frailty in mice - Xinwei Jiao; Hongyu Li; Ting Wang; Hongchen Fu; Shiwu Wang; Hong Liu; Lei Wang; Xiuyun Li; Aijun Deng; Zhijie Li (iScience)
Summary: The gut microbiota modulates aging through metabolic and immune interactions. To characterize microbial changes during aging, we profiled gut microbiota across four stages in male C57BL/6J mice: young-adult, middle-aged, senescent, and frailty. Using 16S rRNA sequencing and targeted metabolomics, we observed a biphasic diversity pattern, with reduced richness in senescence followed by a rebound in frailty. Frailty-stage microbiota showed increased connectivity and enrichment of Lachnospiraceae, alongside short-chain fatty acid (SCFA) depletion, particularly butanoic acid. Functional predictions revealed elevated immune activity and reduced carbohydrate metabolism, linked to specific microbial taxa. These findings highlight a structured remodeling of the gut microbiota during aging, with frailty representing a distinct dysbiotic state associated with metabolic dysfunction. Modulating gut microbial composition may represent a potential strategy to attenuate frailty and promote healthy aging.